PENGARUH CITRA PRODUK DAN KEPUASAN KONSUMEN TERHADAP LOYALITAS PELANGGAN MAKANAN TRADISIONIL DI KOTA AMBON - Grace H. Tahapary (Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2017)
This study aims to determine the effect of brand image and customer satisfaction on customer loyalty of traditional food in the city of Ambon. The population of this study is the consumers who live in the city of Ambon, aged ≥ 17 years, and never eat traditional food more than twice Ambon. Samples were taken using simple random sampling technique. The questionnaire used as a research instrument in order to obtain primary data that can be used to identify the facts or the actual conditions in the field. Data analysis technique used is the Multiple Linear Regression. The results showed that: (1) Image Products and Customer Satisfaction in Customer Loyalty significant positive influence of Traditional Foods in the City of Ambon either simultaneously or partial, and (2) Customer satisfaction is the most dominant variable affecting the Customer Loyalty Traditional Foods in the city of Ambon. Keywords: Product Image, Customer Satisfaction, Customer Loyalty